Kekerasan Simbolik Berita Kriminal di Media Massa - Chazizah Gusnita (Universitas Budi Luhur, 2017)
Violence is not only done physically but can also be symbolic. Symbolic violence is the meaning, logic and beliefs that are biased but subtly and vaguely imposed on the other as true. Symbolic violence is based on a long-established and socially long-standing social expectations and beliefs. Coercion is done smoothly and vaguely so that the public does not realize and feel it as coercion. By hiding the violence, it is hoped that the symbolic violence can be accepted by the audience as something reasonable. Symbolic violence by the media in the form of language, symbols, text, images, and other mass media attributes. Mass media is able to form labeling, stigma, new discourse in society by doing such symbolic violence. The worst thing is that perpetrators and victims of symbolic violence are not aware of the spread of this